Study of linearity and stability of Pb(II)-1, 10-phenanthroline complex with the presence of Fe (II) dan Mg (II) matrix ions using UV-Vis spectrophotometry. Issue 1 (February 2021) - Nisah, K; Ramli, M; Marlina; Idroes, R; Safitri, E
Abstract: The effect of Fe (II) and Mg (II) as matrix ions in the determination of Pb (II) based on 1, 10-phenanthroline complexing agent at pH 7 had been investigated. The objective of this study is to determine the effect of Fe (II) and Mg (II) on the determination of Pb (II) using the complexing agent 1, 10-phenanthroline. The absorbance determination using a spectrophotometer was conducted at a wavelength of 302.5 nm for Pb (II)-1, 10-Phenanthroline. Linear correlation between the investigated absorbance on Pb concentration was represented by a linear equation of y = 0.0131 x + 0.8693 (R 2 = 0.9613). From the linear equation, it was obtained the increase in sensitivity and linearity for Mg (II), as well as the decrease in sensitivity and linearity for Fe (II). It revealed that Fe (II) and Mg (II) affects the analysis of Pb (II) using 1, 10-phenanthroline complexing agent. In order to achieve stability of Pb (II)-1, 10-Phenanthroline, it was compared with Mg (II)-1, 10-Phenanthroline and Fe (II)-1, 10-Phenanthroline. It suggested that Pb (II), Mg (II) and Fe (II) had an equivalent binding strength against 1, 10-Phenanthroline.